Mutualism in Action: CSR Partnerships for Community Development (A Case of PT Pertamina Patra Niaga and Women Farmer Groups Arimbi) - Hayati, Beti Nur; Bagus Budianto; Irfan Hibatulaziz (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2023)
Abstract: The aim of this research is to explore the forms of partnership in the corporate social responsibility (CSR) activities of PT Pertamina Patra Niaga DPPU Adisucipto Yogyakarta and the Women Farmer Group (KWT) Arimbi in community development. The method used in this research is qualitative-descriptive, involving interviews, observations, and documentation. Data analysis follows the interactive research analysis model, including data reduction, data presentation, and drawing conclusions. The results of this research reveal several forms of partnership established in community development. These include collaboration in providing facilities to enhance the productivity of KWT Arimbi, the development of aquaponics and tabulampot farming models, plant cultivation training, administrative support, and organizational assistance. Additionally, there are three business units, namely a lending and borrowing unit, a cultivation and agricultural supplies unit, and a processing unit within KWT Arimbi. The partnership between CSR DPPU Adisucipto and KWT Arimbi in the endeavor to develop the farming group takes the form of mutualism partnership, as both parties contribute effectively to advancing community well-being. PT Pertamina Patra Niaga DPPU Adisucipto Yogyakarta actively contributes through CSR funding, training, and mentoring. Meanwhile, KWT Arimbi actively strives to maximize its potential and the support received with a sense of responsibility for mutual progress. These findings illustrate the positive potential of mutualistic partnerships between the private sector and communities in supporting sustainable agriculture and community empowerment. It is hoped that this can provide a strong foundation for achieving sustainable development goals. Keywords : Mutualism Partnership, Corporate Social Responsibility, community development     Tujuan dari penelitian ini adalah untuk mengekspor bentuk-bentuk kemitraan dalam kegiatan tanggung jawab sosial perusahaan(CSR) PT PERTAMINA Patra Niaga DPPU Adi Sucipto Yogyakarta dan Kelompok Wanita Tani (KWT) Arimbi dalam pengembangan komunitas.. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan melakukan wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan model analisis penelitian interaktif reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah terdapat beberapa bentuk program kemitraan yang terjalin dalam pengembangan komunitas, diantaranya kerja sama penyediaan fasilitas peningkatan produktivitas KWT Arimbi, pengembangan model budidaya aquaponik dan tabulampot, pelatihan budidaya tanaman, dukungan administrasi dan organisasi instansi. Selain itu terdapat 3 unit usaha yaitu unit simpan pinjam, unit budidaya dan saprotan, serta unit pengolahan. Kemitraan antara CSR DPPU Adi Sucipto dan KWT Arimbi dalam upaya pengembangan kelompok tani mengarah pada pada bentuk kemitraan mutualisme. Karena keduanya saling berkontribusi secara baik dalam upaya memajukan kesejahteraan komunitas. PT PERTAMINA Patra Niaga DPPU Adi Sucipto Yogyakarta memberikan berkontribusi aktif dalam melalui dukungan pendanaan CSR, pelatihan dan pendampingan. Sedangkan KWT Arimbi berusaha secara aktif memaksimalkan potensi dan dukungan yang diperoleh dengan penuh tanggung jawab untuk kemajuan bersama. temuan ini menggambarkan potensi positif dari kemitraan mutualisme antara sektor swasta dan komunitas dalam mendukung pertanian berkelanjutan dan pemberdayaan komunitas diharapkan ini bisa memberikan landasan kuat untuk mencapai tujuan pembangunan berkelanjutan. Kata Kunci: Kemitraan Mutualisme, Tanggung Jawab Sosial Perusahaan, pengembangan masyarakat